Variable Neighborhood Search: The power of change and simplicity. (July 2023) - Brimberg, Jack; Salhi, Said; Todosijević, Raca; Urošević, Dragan
Abstract: This review discusses and analyses three main contributions championed by Professor Mladenović. These include variable neighborhood search (VNS), variable formulation space (VFS), and finally, the less-is-more approach (LIMA). These three methodologies share two important ingredients, namely, simplicity and change. Given that Professor Mladenović is widely known for VNS, we will focus mainly on this methodology and its developments as well as a sampling of successful applications. This is followed by a shorter discussion covering VFS and LIMA. We introduce several remarks throughout the text to highlight certain aspects while also suggesting challenging research areas to examine.